Penerapan Healing Environment Pada Redesign Interior Poliklinik Dan UGD Puskemas Baturiti 1 - Simanungkalit, Pavioline Sandra Bentha; Prihandono , Dion Eko; Dewi, Putu Surya Triana (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2025)
The facilities within the emergency room  and outpatient clinic at Puskesmas Baturiti 1 require enhancement to optimize healthcare services. Key aspects such as patient handling efficiency, circulation, and accessibility need to be addressed. Circulation should be improved to ensure that patient and medical staff flows are separated, while accessibility must cater to the comfort of all users, especially the elderly, individuals with disabilities, pregnant women, and children. Data collection was conducted through direct observation, interviews with staff, and document studies related to health service standards and government regulations. This methodology ensures that the resulting design meets operational needs, supports efficient circulation, and complies with healthcare service standards, particularly for the emergency and outpatient departments. Data analysis highlights the need for improvements in circulation, facilities, and accessibility. Solutions include optimizing spatial layout, adding facilities in accordance with service standards, and enhancing accessibility through ramps and barrier-free pathways. The theme and concept of a healing environment is applied through design elements that promote comfort, such as natural lighting, calming colors, and green spaces. This approach aims to create an environment conducive to patient recovery while improving the overall quality of healthcare services at Puskesmas Baturiti 1.